Effectiveness Of Use Of Antihypertensive Drug In Inpatient Stroke Patients In Hospital Tabanan Regency - Ni Nyoman Wahyu Udayani; Ni Luh Putu Dewi Purnama Sari (Institute of Computer Science (IOCS), 2022)
Cardiovascular disease is a disease of the heart and blood vessels. Because the cardiovascular system is very vital, cardiovascular disease is very dangerous for health. One of the cardiovascular diseases is a stroke. The prevalence of stroke in Indonesia reaches 8.3 out of 1000 populations. This prevalence rate increases with increasing age. Indonesian National Data shows that stroke is the highest cause of death, which is 15.4%. Blood pressure management is a strategy to prevent stroke and reduce the risk of recurrence in ischemic stroke and hemorrhagic stroke. The purpose of this study was to determine the effectiveness of the use of antihypertensive drugs in patients with ischemic and hemorrhagic stroke inpatient care at hospital Tabanan seen from the patient's blood pressure. This research is a type of descriptive research with data collection carried out retrospectively. This study was conducted on 53 patients with ischemic stroke and hemorrhagic stroke using antihypertensive drugs. The results of the study on the effectiveness of the use of blood pressure-based antihypertensive drugs in ischemic stroke decreased systolic blood pressure by ≤5 mmHg by 8 patients (15.09%), decreased systolic blood pressure> 5 mmHg by 1 patient (1.89%). In hemorrhagic stroke decreased systolic blood pressure ≤ 5 mmHg as many as 25 patients (47.17%), decreased systolic blood pressure> 5 mmHg as many as 11 patients (20.76%) and in patients who experienced an increase in blood pressure occurred as many as 8 patients (15,09%).